2013
DOI: 10.3109/17453674.2013.810518
|View full text |Cite
|
Sign up to set email alerts
|

Effect of femoral head size on risk of revision for dislocation after total hip arthroplasty

Abstract: Background and purpose Previous population-based registry studies have shown that larger femoral head size is associated with reduced risk of revision for dislocation. However, the previous data have not included large numbers of hip resurfacing arthroplasties or large metal-on-metal (> 36-mm) femoral head arthroplasties. We evaluated the association between femoral component head size and the risk of revision for dislocation after THA by using Finnish Arthroplasty Register data.Patients and methods 42,379 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 20 publications
2
25
1
Order By: Relevance
“…Femoral head size was not an independent risk factor for early dislocation in our study. This contradicts recent registry studies that have found that increased femoral head size reduces the risk of dislocation ( Hailer et al 2012 , Kostensalo et al 2013 ), and also level-1 studies that have also shown a reduced risk of dislocation with larger femoral heads ( Garbuz et al 2012 , Howie et al 2012 ). One possible explanation for this is our study design.…”
Section: Discussioncontrasting
confidence: 61%
“…Femoral head size was not an independent risk factor for early dislocation in our study. This contradicts recent registry studies that have found that increased femoral head size reduces the risk of dislocation ( Hailer et al 2012 , Kostensalo et al 2013 ), and also level-1 studies that have also shown a reduced risk of dislocation with larger femoral heads ( Garbuz et al 2012 , Howie et al 2012 ). One possible explanation for this is our study design.…”
Section: Discussioncontrasting
confidence: 61%
“…The frequency and RR of revision due to dislocation was, however, lower for MoM bearings than for MoP bearings. In a recent study from the Finnish Arthroplasty Register, the RR of revision due to dislocation was 0.09 (CI: 0.05–0.17) for head sizes larger than 36 mm compared to 28 mm ( Kostensalo et al 2013 ). Thus, the low risk of revision of MoM THA due to dislocation might be explained by the fact that MoM THAs in that study mainly had head sizes larger than 37 mm.…”
Section: Discussionmentioning
confidence: 99%
“…The main justification for using large-diameter-head (LDH) MoM bearings in THA was less wear and the hope of lower revision rates. However, a lower risk of revision has only been found for revision due to dislocation ( Kostensalo et al 2013 ), whereas the total risk of revision has been found to be increased in some studies ( Smith et al 2012 , Huang et al 2013 ). In addition, LDH MoM was introduced in order to achieve increased range of motion and better function ( Burroughs et al 2005 , Davis et al 2007 ), but that has not been shown clinically ( Penny et al 2013 ).…”
mentioning
confidence: 99%
“…This undoubtedly reflects the commonly held tenet that the reason for dislocation must be clearly ascertained and addressed; a single approach to solve the problem will often fail. The option of using larger femoral heads with highly crosslinked polyethylene acetabular liners appears to be an increasingly successful strategy to reduce dislocation in both primary THA and in the revision setting [1,13,14,18,25,27,29].…”
Section: Discussionmentioning
confidence: 99%